LITERATURE REVIEW : PENERAPAN MANAJEMEN RISIKO DI UNIT FILING - Vivi Anika Retno Mumpuni; Sri Sugiarsi; Tunjung Bayu Sinta (Sekolah Tinggi Ilmu Kesehatan Mitra Husada Karanganyar, 2021)
Abstract Risk is the possibility of unwanted or unexpected adverse effects in an activity. These risks can have a negative impact on officers who are present during activities, especially in theunit filing. There are several risks of work accidents experienced byworkers, filing such as fingers with staples attached to medical record documents,workers filing can get cough if they take or return medical record documents without wearing a mask. The purpose of the study was to determine the application of risk management in theunit filing. The research method used is Literature Review with a search strategy usingresults criteria Google Scholarwith the keywords